PENGARUH POROSITAS BUATAN PADA ADSORBER TERHADAP KUALITAS TRANSFER PANAS DAN MASSA - Sukatiman Sukatiman; Dewanto Harjunowibowo (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
On the cooler machine power heat, performance machine efficiency (COP-Coefficient of Performance) isaffected by adsorber capacity in adsorbing numbered refrigerant and releasing in fast periode. the velocity willincrease if it has velocity transfered heat and high mass.This research focused on knowing variation effect adsorbed of solid porousity adsorber versus head transfer rateand high mass. Research methods used many relevance references.The result of this research is that more increasing porousity volume caused high rate of mass transferredand high heat. Yet if to many porousity made volume of adsorber smaller so that mass transferred achieve optimumand decreased.